COLLABORATIVE LEARNING: Model Pembelajaran Dalam Upaya Meningkatkan Literasi Informasi Mahasiswa Jurusan Ilmu Perpustakaan dan Informasi Melalui Belajar secara Kolaboratif - Haqqi, Athiatul (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2017)
This article aims to know about the learning process on majors lecture at library and Information science departement. This Research focussed on applying systems model the colaborative learning in the development of ability of students’s information literacy for student of library and information science departement of the Adab and Humaniora Faculty of the state Islamic University of SulthanThaha Saifuddin Jambi. The result of this research showed that the learning process condition of students of the fifth semester (A/B/C) of 2016/2017 academic was good even to lower category. The describt of learning result for the student’s ibrary and information science of the fifth (A/B/C) on 2016 / 2017 academic for six lectures were goodness have visible with the value estimation obtained by B or B+ predicate or 7 - 7,99 predicate. The factors that influenced lecturer in learning process to the students of the fifth semester ( A/B/C) of Majors of Library Science are; teaching method of lecturer, support of literatures; and the systems of teaching planning for lecturer. The collaborative learning model what expected in the improving efforts of the student information literacy are; Engagement, Exploration, Transformation, Presentation, and Reflection.